Relaxation of guinea-pig trachea by sodium nitroprusside: cyclic GMP and nitric oxide not involved. - Sadeghi-Hashjin, G. (1996)
1. Sodium nitroprusside (SNP) completely relaxed the guinea-pig isolated, perfused trachea in a concentration-dependent manner. Although SNP was less potent by about 2 orders of magnitude, its maximal effect was 25% higher compared to isoprenaline. 2. SNP (3.2 microM) increased cyclic GMP levels by 300% and relaxed guinea-pig isolated, perfused trachea by 54%. The SNP-induced relaxations of the preparations were not affected by the guanylate cyclase inhibitor, methylene blue. Moreover, zaprinast, a cyclic GMP-specific phosphodiesterase inhibitor which was supposed to enhance SNP-induced relaxations, decreased the maximal relaxation by 22% (P < 0.001). 3. In contrast, 8Br-cyclic GMP (10 microM) increased the cyclic GMP levels by 1100% without inducing a marked relaxation. 4. SNP (10 microM) and S-nitroso-N-acetylpenicillamine (SNAP; a direct donor of nitric oxide; 10 microM), relaxed the tissues by 75% and 25%, respectively, without any nitric oxide (NO) release by SNP (< 1 pmol 100 microliters-1), but a substantial NO release by SNAP (560 pmol 100 microliters-1). 5. It is concluded that the SNP-induced tracheal relaxations are probably not mediated by cyclic GMP and NO.